Apertura ácida de sapogeninas espirostánicas 25R en microondas - Mendoza Juárez, Vianey Angélica (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
From previous studies within our research group, it is known that the treatment of spirostanic sapogenins in an acid medium generates different rearrangements on the lateral side chain, oriented towards the formation of different rings on the steroidal frameworks, to which several biological properties have been attributed, besides the ease of these towards lateral side chain opening, has made them synthons of great synthetic value in the obtaining of steroidal drugs, as well as analogues of natural products biologically interesting. Due to the above, in the present work a new methodology is proposed in order to generate steroidal derivatives with varied structure, through different reactions in an acid medium using as starting material, diosgenin acetate (17) and 23-ketodiosgenin acetate (86), promoted by microwave as a strategy of green synthesis. The synthesized compounds were characterized by spectroscopic (IR, 1D and 2D NMR) and spectrometric (HR-MS) methods for their structural analysis. In the case of acid opening of diosgenin acetate (17) with ZnCl2, when 1,2-DCE is used as solvent, four compounds are obtained, two cholestanic derivatives 87, 88, an epoxycholestene derivative 89 and a furosthenic compound 90, this last as major product, followed by cholestanic compound 87. Additionally, it was found that by using THF as a solvent for the same reaction, diacetylated pseudodiosgenin 12 is regioselectively obtained; which is a key intermediate in the synthesis of hormones on an industrial scale, which demonstrates the versatility of spirostanic structures towards the formation of several derivatives according to the reaction conditions used.

De estudios previos en nuestro grupo de investigación, se sabe que el tratamiento de sapogeninas espirostánicas en medio ácido genera diferentes rearreglos orientados hacia la formación de diferentes anillaciones en el esqueleto esteroidal, a los cuales se les ha conferido diversas propiedades biológicas, además de la susceptibilidad de estas hacia la apertura de la cadena la cadena lateral, lo que las convierte en sintones de gran valor sintético en la obtención de fármacos esteroidales, así como análogos de productos naturales de interés biológico. Debido a lo anterior, en el presente trabajo se propone una nueva metodología para generar derivados esteroidales de estructura variada, mediante de reacciones de apertura en medio ácido, del acetato de diosgenina (17) y del acetato de 23-cetodiosgenina (86), esto a través de microondas como estrategia de síntesis verde. Los compuestos sintetizados fueron caracterizados mediante métodos espectroscópicos (IR, RMN en 1D y 2D) y espectrométricos (HR-MS) para su análisis estructural. Para el caso de la apertura ácida del acetato de diosgenina (17) con ZnCl2, al usar 1,2-DCE como disolvente, se obtienen cuatro compuestos, dos derivados colestánicos 87, 88, un derivado epoxicolesténico 89 y uno con estructura furosténica 90, siendo este último el producto mayoritario, seguido del colestano 87. Adicionalmente, se encontró que al emplear THF como disolvente para la misma reacción, se obtiene de manera regioselectiva la pseudodiosgenina diacetilada 12, intermediario clave en la síntesis de hormonas a escala industrial, lo que demuestra la versatilidad de las estructuras espirostánicas hacia la formación de diferentes derivados según las condiciones de reacción empleadas.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias Químicas
Keywords: info:eu-repo/classification/cti/2; IIQB-R-M-2021-1463; Diosgenina; 23-cetosapogenina; Espirocetales; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6520